ANALISIS PERWATAKAN DALAM NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR - Desputri, Sherly; Bahardur, Iswadi; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
This study focused on the characterization in the novel Small Letters to God Agnes Davonar work. Formulation of the research problem "How dispositive Analysis in Novel Small Letters to God Agnes Davonar work?           This study uses descriptive analysis . This study collected data descriptive phases: (1) read and understand the novel, (2) marking the novel, and (3) inventory data.Number of characters involved in the novel Small Letters to God Agnes Davonar work as many as 16 people. (1) Keke he has the unyielding nature , full of gratitude, strong , clever , patient , and active. (2) Pak Joddy as a father has unyielding nature, spirit, loyal, and caring. (3) Mr. Iyus as a driver possesses a swift, loyal, and cheerful. (4) Chika as a brother has an independent nature. (5) as the sister Kiki has a good nature. (6) Mothers parental Keke has a loyal nature. (7) as a lover Andi Keke has a loyal nature, and attention. (8) Bibi as domestic servants have a loyal nature. (9) as a neighbor and sister Princess Keke Class yangbaik properties. (10) Fahda as friend Keke has siafat attention and confidence. (1) Shifa as friend Keke has a passionate nature. (12) Angel as a friend Keke has properties that scoffers. (13) Professor Mukhlis as a doctor has a friendly nature , and never give up. (14) Professor Peng Shuai as the doctor has a friendly nature and never give up. (15) Ana as a psychologist has a property firm, and (16) as Sister Sister has a friendly nature.